PEMBELAJARAN BERBASIS PICTORIAL RIDDLE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMPN 1 PEKANBARU PADA MATERI CAHAYA DAN ALAT OPTIK - Isti’anah Rosta; M. Nor M. Nor; Zulhelmi Zulhelmi; Zulfahmini Zulfahmini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the increase in learning motivation of class VIII students of SMP Negeri 1 Pekanbaru by applying learning based on Pictorial Riddle to light material and optical devices. The type of research used is pre-experiment with the research design is one group pretest-posttest design. The research subjects were class VIIIHN students of SMP Negeri 1 Pekanbaru Academic Year 2018/2019 which amounted to 36 students. The research data is learning motivation data cosisting of pretest and posttest scores through the application of learning based on Pictorial Riddle. The instrument used to collect data in this study was the John Keller ARCS motivation questionnaire. Data were analyzed descriptively through the calculation of N-Gain using Hake’s motivation criteria and formulas. The results of the analysis of the data obtained are, the are changes in the average score of the initial motivation score. Obtained an increase in the average score of student learning motivation for all indicators with N-Gain of 0,54 moderate categories. So that it can be concluded that there is an increase in student learning motivation before and after applying learning based on Pictorial Riddle to light material and optical devices.Key Words: Pictorial Riddle, Learning Motivation, Light and Optical Devices.